The factors influencing production and economic efficiency of beef cattle farm in Grobogan Region, Central Java - Ekowati, T.; Prasetyo, E.; Handayani, M. (Diponegoro University, 2018)
The study was aimed to analyze the on-farm agribusiness subsystem approach at farm household, to analyze beef cattle production influencing factors and to analyze economic efficiency of beef cattle farm. The method use for research was survey method at Wirosari District and Purwodadi District, Grobogan Regency as research location. Each district was determined two villages to obtain data from respondent. Quota sampling method was use for determination the number of beef cattle farm household without a counting of population as a sampling frame. The number of respondent for each village was 20 farmers, so the total respondent was 80 farmers. Data were analyzed descriptively for on farm sub-system agribusiness approach, multiple linear regression and economic efficiency. The research result showed that the on-farm agribusiness subsystem was on moderate to good condition, the influencing factors of production were breed, forage, concentrate, health, reproduction, labor, year of farming and agribusiness implementation. The value of reproduction efficiency was 8.975 higher than 1, it was not efficient. The efficiency of farm scale, forage, concentrate, health and labor were 0.352; 0.128; 0.0148; 0.0235 and 0.0834 respectively less than 1, and it had not been efficient yet. The conclusion of research was the agribusiness implementation in beef cattle farming was in moderate and good criteria and gave the benefit to farmers. Production factors of farm scale, forage, concentrate, health, reproduction, labor, years of farming and agribusiness implementation were influence to the beef cattle production. The efficiency of farm scale, forage, concentrate, health, and labor on the beef cattle farm were not been efficient yet, while reproduction became an inefficient production factor.